Retailer Segmentation as A Strategy for B2B Marketing using A Two-Level Clustering Analysis - Prita Prasetya; Mukhamad Najib; Febrina Mahliza (Universitas Prasetiya Mulya, 2022)
This paper aims to explore the possibility of identifying retailer segments. Data is the foundation of segmentation that helps identify the critical value drivers, select the appropriate engagement level and decide the retailer engagement. This study proposes a new approach that considers two-stage clustering for retailer segmentation and behavioural analysis among building materials companies in Indonesia. The alignment could provide a practical managerial approach to finding competitive advantage and a better understanding of sales opportunities. Retailer segmentation can be done differently from the most relevant sales perspective. In this study, we propose an alternative method for retailer segmentation based on two-stage clustering. First, segmentation is based on three categories of the size of order: a very potential group of customers in which the order size is large, a middle group and a group where the order size is small. Second, segmentation based on personal value is a relational perspective that considers the behavioural analysis from the manufacturer-retailer relationship.